2018
DOI: 10.3233/npm-181732
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved mothers’ and fathers’ perceptions of a legacy intervention for parents of infants in the NICU

Abstract: Participants reported that a legacy-making intervention via digital storytelling would be feasible, acceptable, and beneficial for NICU parents. Study results support the need and desire for legacy-making services to be developed and offered in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…42,5658 Similarly, caregivers of adult patients and parents of pediatric patients shared acceptance of and interest in participating in legacy interventions with their seriously ill loved ones, seeing value both for their own coping and that of the patient. 5658…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42,5658 Similarly, caregivers of adult patients and parents of pediatric patients shared acceptance of and interest in participating in legacy interventions with their seriously ill loved ones, seeing value both for their own coping and that of the patient. 5658…”
Section: Resultsmentioning
confidence: 99%
“…Akard et al, 57 USA Mixed methods RCT using the Personal Orientation Inventory and descriptive evaluation No statistically significant differences between the two groups before or after the sessions, but the life review group felt the sessions increased their self-actualization through concern for others. enhancing patient sense of value and dignity, promoting effective interaction, and attending to unfinished business.…”
Section: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date no studies have been published confirming these results, with this remaining a potential future subject of research. Finally, although with fewer references, mention should also be made of the intervention involving periodic telephone calls during the first year of the bereavement process (Akard et al 2018;Covington 2009;DiMarco et al 2001;Gibson et al 2011;Levick et al 2017;Reilly-Smorawski et al 2002;Roose & Blanford 2011). This was also considered a good way of assisting parents in the grieving process and one which they appreciate as it demonstrates the continued concern about their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Legacymaking has been explored in both adult and pediatric populations. [20][21][22][23][24][25][26][27][28][29][30][31][32] Legacy-making in adults has been shown to increase patients' sense of dignity, purpose, meaning, and will to live, while decreasing suffering and depressive symptoms. 22,28,32 In our previous work, hospital staff and parents reported that legacymaking improved quality of life (QOL), communication, and coping among children with cancer (ages 7-17).…”
Section: Introductionmentioning
confidence: 99%